Numerical simulation of damages to underground cavern due to explosion - Fan, Sau Cheong (2008)
This report consists of two part. Part A reports the study on shock wave propagation in jointed rock. Part B reports the feasibility study of using Discrete Element method (DEM) to stimulate fragmentation.